Effect of care for child development training on cadres’ knowledge, attitude, and efficacy in Yogyakarta, Indonesia - Akhmadi, Akhmadi; Sunartini, Sunartini; Haryanti, Fitri; Madyaningrum, Ema; Sitaresmi, Mei Neni (Belitung Nursing Journal, 2021)
Background: Stunting is a common malnutrition problem among children in the world. The Care for Children Development (CCD) intervention is a strategy to reduce stunting. Objective: This study aimed to identify the effect of culturally modified CCD training on the knowledge, attitude, and efficacy (KAE) of cadres about stunting in the community.Methods: We conducted a community-based study with a quasi-experimental research design using a comparison group. The study was conducted from March 2018 to February 2019 at three Public Health Centers in Yogyakarta, Indonesia. The total participants were 69 in the intervention group and 53 in the comparison group. Cadres in the intervention group received two days of training on a culturally modified CCD guideline. In contrast, cadres in the comparison group received a brief explanation (a one-day training) on that program. The nurses from three public health centers were facilitators in this training. Knowledge and self-efficacy were assessed using a modified Caregiver Knowledge of Child Development Inventory and General Self-efficacy Scale, respectively. Data were analyzed using Mann-Whitney U and Wilcoxon tests.Results: All 122 cadres completed the training. In the intervention group, CCD training significantly increased cadres’ knowledge (median score 14 vs. 11), attitude (58 vs. 55), and efficacy (30 vs. 28), all with p <0.001. In the comparison group, the short explanation of CCD significantly improved cadres’ knowledge (median score 12 vs. 10) and efficacy (29 vs. 27) but not their attitude. The delta or change in score before and after CCD training for cadres’ attitude in the intervention group was significantly higher than that of the comparison group (3.78 vs. 0.72; p = 0.050). Conclusion: A culturally modified CCD training significantly improves cadres’ KAE in the intervention group and cadres’ knowledge in the comparison group. The learning delivery methods with demonstrations and role-plays significantly improved the cadres’ attitudes as health educators for stunted mothers in the community. For sustainability, community health nurses should regularly collaborate with cadres to improve the nutritional status of children in their area.